Thermodynamic Aspects of the Use of Heat Exchangers in Low-Temperature Power Systems - Trotsenko, A.V. (Journal of Advanced Thermal Science Research, 2021)
The problems of thermodynamic analysis associated with the heat exchangers that used in cryogenic technology are discussed. A method and an algorithm for calculating the components of losses from irreversibility in these heat exchangers are proposed. The exergy method of thermodynamic analysis was used to calculate the components of these losses for some two-flow heat exchangers. The investigation of the obtained calculation results is presented.